Science Proclaims Materialism Is Dead by Adil Kabbaj. A Revolutionary Synthesis of Physics, Philosophy, and Information Theory - Tuna, Erkan (Journal of NeuroPhilosophy, 2026)
Adil Kabbaj’s monumental work Science Proclaims Materialism Is Dead: From Substantialism to Non-Substantialism (Iff Books, 2026) represents an extraordinarily ambitious, philosophically daring, and interdisciplinary deep exploration that seeks to demonstrate, through a comprehensive examination of contemporary physics, that materialism—the dominant worldview of the modern era—has been scientifically and philosophically invalidated. Drawing on decades of research in quantum mechanics, quantum field theory, quantum gravity, and information theory, the author argues persuasively that the universe is not composed of matter or any other substance, but rather of activity, energy, action-information, and ultimately, relational agents (fail/agent). The book constitutes a genuinely significant contribution to the growing literature challenging materialist metaphysics from within the framework of rigorous scientific analysis. What fundamentally distinguishes Kabbaj’s work from others in this field is its systematic integration of multiple interpretative traditions in quantum physics—from Bohr and Heisenberg through Bohm, Wheeler, Rovelli, and far beyond—synthesizing them into a coherent, substantiality-transcending (non-substantialist) worldview. In this respect, the work not only summarizes existing interpretations but goes beyond them to present an original metaphysical framework.